Impact of health education on knowledge retention among caregivers of hypertensive patients: A prospective cross-sectional study in rural Malawi - Chikondi Maluwa; Sitalire Kapira; Hataichanok Chuljerm; Wason Parklak; Kanokwan Kulprachakarn (PLoS ONE, 2025)
Hypertension is a widespread and life-threatening condition affecting one-third of adults globally. In low- and middle-income countries, like Malawi, the burden of hypertension is escalating due to inadequate healthcare resources and lifestyle changes. Family members often become primary caregivers, playing a crucial role in managing hypertension through support and adherence to treatment. This study examined caregivers’ knowledge retention by evaluating their pre- and post-health education knowledge levels. This was a prospective cross-sectional study in Neno, Malawi, a rural setting. 422 caregivers were enrolled from the Integrated Chronic Care Clinic (IC3). A structured questionnaire was used to collect baseline, post-health education, and week six data. Using SPSS V 22.0, comparison of knowledge, attitude, and practices (KAP) scores, correlation between KAP and between KAP and social demographic characteristics were done using Wilcoxon signed-rank test, Pearson correlation, and independent t-test respectively. Among the 422 caregivers who participated in the study, 267 (63.2%) were females and mean age was 44.94 years. The baseline mean knowledge level score was 9.5 (38.0%) and rose to 21.08 (84.3%) p = 0.000 immediate post-health education and a 2.1% decrease 20.54 (82.2%) p<0.001 at week six from the immediate post health education score. Attitude improved from 16.76 (93.1%) at baseline to 17.74 (98.6%) at the six-week mark. Similarly, the mean practice score rose from 25.24 (78.9%) at baseline to 27.42 (85.7%) at week six. There was a positive correlation between KAP while age had a negative correlation with knowledge (r = -0.146; p = 0.003). There was a significant difference between different education levels on knowledge retention p = 0.009. There was a positive and good knowledge retention among caregivers of hypertensive patients after health education at the week six mark. With improved knowledge and the ability to retain it resulting in improved attitude and practices, caregivers are a cornerstone for continued and improved hypertension care for the patients.